Strontium Insertion in Methylammonium Lead Iodide: Long Charge Carrier Lifetime and High Fill‐Factor Solar Cells. Issue 44 (22nd September 2016) - Pérez‐del‐Rey, Daniel; Forgács, Dávid; Hutter, Eline M.; Savenije, Tom J.; Nordlund, Dennis; Schulz, Philip; Berry, Joseph J.; Sessolo, Michele; Bolink, Henk J.
Abstract : The addition of Sr 2+ in CH3 NH3 PbI3 perovskite films enhances the charge carrier collection efficiency of solar cells leading to very high fill factors, up to 85%. The charge carrier lifetime of Sr 2+ ‐containing perovskites is in excess of 40 μs, longer than those reported for perovskite single crystals.